Potensi saponin pada kacang-kacangan sebagai pangan fungsional pencegah penyakit diabetes melitus tipe-2 - Naufal Muwaffaq; Mustika Nuramalia Handayani (ARGIPA (Arsip Gizi dan Pangan), 2022)
Type 2 Diabetes Mellitus is a chronic disease that cannot be cured but has the potential to be prevented and controlled. Diabetes is the 9th leading cause of death in the world. The management of Type-2 Diabetes Mellitus can be done non-pharmacologically using natural compounds, one of which is saponins obtained from nuts. Saponins acts as inhibitors of the activity of the Î±-glucosidase enzyme which functions to convert carbohydrates into glucose so that glucose absorbed by the small intestine can be blocked. This study aims to determine the potential of saponins from nuts. This research method is literature study of 78 articles and filtered about 15 articles with the keywords saponin content in nuts. The results of this study prove that there is potential for saponins found in nuts and the greatest potential for saponins is found in soybeans (glycine max), navy beans (phaseolus vulgaris), and red beans (phaseolus vulgaris).